2023
DOI: 10.1007/s44246-023-00042-8
|View full text |Cite
|
Sign up to set email alerts
|

Different responses of agroecosystem greenhouse gas emissions to tillage practices in a Chinese wheat–maize cropping system

Abstract: To mitigate greenhouse gas (GHG) emissions of intensified agriculture, conservation practices are gradually being implemented in Chinese wheat–maize cropping systems. However, the effects of different tillage practices on agricultural field GHG emissions and subsequent global warming potential (GWP) are poorly documented. In this study, a three-year field experiment was conducted from 2019 to 2021 to assess the effects of tillage on the emissions of carbon dioxide (CO2), methane (CH4), nitrous oxide (N2O), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 66 publications
3
13
0
Order By: Relevance
“…Previous studies [3,4,[80][81][82] have demonstrated that SEM is a powerful and flexible method for analyzing the complex relationships among multiple and diverse variables affecting the agricultural sector. SEM allows researchers to model intricate interactions among observed and unobserved variables, making it well suited for testing and validating complex theoretical models, as emphasized by Garson [79] and Hair et al [78].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies [3,4,[80][81][82] have demonstrated that SEM is a powerful and flexible method for analyzing the complex relationships among multiple and diverse variables affecting the agricultural sector. SEM allows researchers to model intricate interactions among observed and unobserved variables, making it well suited for testing and validating complex theoretical models, as emphasized by Garson [79] and Hair et al [78].…”
Section: Methodsmentioning
confidence: 99%
“…SEM enables the simultaneous evaluation of multiple variables and their interdependencies, making it suitable for studying the multidimensional dynamics of digital technology's impact on sustainable production and consumption, as well as GHGs in agriculture [103]. Previous research in the field of agriculture has successfully employed SEM in investigating influences among heterogeneous variables [104][105][106].…”
Section: Methodsmentioning
confidence: 99%
“…SEM provides several advantages in this context. Firstly, it allows for testing hypotheses derived from the theoretical model, enabling researchers to assess the direct and indirect effects of digital technologies on various aspects of sustainable production and consumption [105]. Secondly, SEM enables the integration of multiple data sources, such as DESI reports, Sustainable Development Reports, and the Eurostat database [107].…”
Section: Methodsmentioning
confidence: 99%
“…Soil tillage is one of the operations with the highest energy consumption, emitting a large amount of GHG (Li et al, 2023). Currently, traditional tillage systems have high fuel consumption, while optimized tillage systems can save signi cantly in terms of energy without compromising crop productivity (Jankowski et al, 2023).…”
Section: A-2mentioning
confidence: 99%